Functional morphology of the tetra fish Astyanax lacustris differs between divergent habitats in the Pantanal wetlands - Costa-Pereira, R. [UNESP]; Araujo, M. S. [UNESP]; Paiva, F.; Tavares, L. E. R. (Wiley-Blackwell, 2016)
This study investigated whether the body morphology of the tetra fish Astyanax lacustris ( previously Astyanax asuncionensis) varied between populations inhabiting one lagoon ( a lentic, shallow environment, with great habitat complexity created by aquatic macrophytes) and an adjacent river ( a deeper, lotic environment where aquatic macrophytes are scarce) in a seasonally flooded wetland, despite population mixing during the wet season. Morphological differences matched a priori predictions of the theory relating functional body morphology and swimming performance in fishes between lagoon and river habitats. Observed morphological variation could have resulted from adaptive habitat choice by tetras, predation by piscivores and adaptive phenotypic plasticity during development. (C) 2016 The Fisheries Society of the British Isles
Keywords: flood pulse; floodplain lagoon; phenotypic divergence